55 tokoh Indonesia asal Minangkabau di pentas nasional - Saydam, Gouzali (Bandung : Alfabeta, 2009)
Biography of fifty-five Minangkabau prominent figures and their contribution to the nation
Bibliography : p. 263-266
Keywords: Minangkabau (Indonesian people) -- Biography